THEORETICAL ASPECTS OF MANAGEMENT OF MARKETING ACTIVITIES OF THE ENTERPRISE - YADUKHA, Sergey; YABLONSKII, Taras; KRUK, Sergii; KUCHANSKA, Tetiana (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines the concepts of "marketing" and "marketing management", analyzes the main concepts of marketing and defines the relationship between marketing and management at the enterprise. This study aims to provide a deep understanding of the key aspects of marketing activities and their integration with general management processes to achieve sustainable commercial success. In the scientific literature, various definitions are given to understand the essence of "marketing". From the given definitions, certain approaches can be distinguished, which include: functional approach, process approach, socio-management approach, entrepreneurial approach, strategic approach, behavioral approach and social approach. In our opinion, marketing should be understood as a complex and multifaceted process that includes market research, product development, pricing, organization of distribution and promotion in order to meet consumer needs and achieve company goals. The development of marketing was carried out within the framework of marketing concepts, in particular: improvement of production; product improvement; intensification of efforts; classic marketing; relationship marketing; marketing deals; strategic marketing; maxi-marketing; mega-marketing. The study of the essence of the concept of "marketing management" allows us to distinguish the following approaches, in particular: functional approach, process approach, organizational approach, systemic approach, adaptive approach and interactive approach. In our opinion, marketing management should be understood as the process of planning, analysis, implementation and control of the enterprise's marketing activities in order to achieve its strategic goals. Marketing and management and their relationship play a key role in ensuring the success of the enterprise. Effective integration of marketing strategies with management processes allows enterprises to adapt to market conditions, satisfy customer needs and achieve their business goals.
Keywords: marketing; marketing management; marketing concepts; management